Policy Triangle Analysis of Stunting Issues in Urban Areas: A Case Study of Yogyakarta City - Wigati, Maria; Ciptanurani, Ceria (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2023)
Stunting reduction is one of Indonesia’s major projects. While one-size-fits-all regulations were no longer promoted, understanding the characteristics of each region imposed a strong policy foundation. Many studies had been conducted in rural areas, but the analysis of urban areas was scarce. A study was conducted in Yogyakarta City to understand the characteristics of stunting intervention, despite the high human development index, education level, and access to health facilities. This made it important to examine the characteristics of stunting reduction efforts, based on the analysis of the contents, contexts, processes, and actors involved, in Yogyakarta City, to help with its ambition for zero stunting. A desk review and focus group discussion were conducted involving four local government staff, consisting of the Regional Planning and Development Agency, Health Office, and Office of Women's Empowerment, Child Protection, and Population Control and Family Planning, which were elaborated with literature following the policy triangle framework. A total of 13 open-access official documents and dashboards were obtained for analysis. Decrees from the local government showed a strong commitment to ending malnutrition. While most intervention packages were similar to those across Indonesia, targeted interventions for specific subjects were needed to support people who were unable to be covered by general services. Furthermore, Yogyakarta City has smaller open spaces than other districts in the province, a contradictory low nutrition awareness despite high school participation, and other factors were cross-linked with its culture in the community, implementer, to the authority levels. Stunting reduction programs were multisectoral, involving not only government offices but also non-government, mass media, community, private sectors, and academia. This study is expected to provide lessons learned for decision-makers, private sectors, academia, and public health practitioners to implement good collaboration in stunting reduction efforts.